Species-specificity of the secondary biosynthetic potential in Bacillus - Yin, Qun-Jian; Ying, Ti-Ti; Zhou, Zhen-Yi; Hu, Gang-Ao; Yang, Cai-Ling; Hua, Yi; Wang, Hong; Wei, Bin (Frontiers in Microbiology, 2023)
Although Bacillus species have produced a wide variety of structurally diverse and biologically active natural products, the secondary biosynthetic potential of Bacillus species is widely underestimated due to the limited number of biosynthetic gene clusters (BGCs) in this genus. The significant variation in the diversity and novelty of BGCs across different species within the Bacillus genus presents a major obstacle to the efficient discovery of novel natural products from Bacillus. In this study, we investigated the species-specificity of BGC, gene cluster family (GCF), and their predicted metabolite scaffolds in 6379 high-quality Bacillus genomes. Our results revealed a certain degree of speciesspecificity in the distribution of BGCs in Bacillus, which was mainly contributed by siderophore, type III polyketide synthase (T3PKS), and transAT-PKS BGCs. B. wiedmannii, B. thuringiensis, and B. cereus are rich in RiPP-like and siderophore BGCs, but lack T3PKS BGCs, while B. amyloliquefaciens and B. velezensis are abundant in transAT-PKS BGCs. These Bacillus species collectively encode 77,541 BGCs, with NRPS and RiPPs being the two most dominant types, which are further categorized into 4291 GCFs. Remarkably, approximately 54.5% of GCFs and 93.8% of the predicted metabolite scaffolds are found exclusively in a single Bacillus species. Notably, B. cereus, B. thuringiensis, and B. velezensis exhibit the highest potential for producing species-specific NRPS and PKS bioinformatic natural products. Taking two species-specific NRPS gene clusters as examples, the potential of Bacillus to synthesize novel species-specific natural products is illustrated. This study highlights the speciesspecificity of the secondary biosynthetic potential in Bacillus and provides valuable insights for the targeted discovery of novel natural products from this genus.